THE STRATEGIES OF IMPROVING EFFECTIVE IMPLEMENTATION OF THE COMPETENCE-BASED CURRICULUM IN SECONDARY SCHOOLS IN TANZANIA: THE CASE STUDY OF TABORA REGION - Assey, Ernest S. (Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to investigate what stakeholders in education thought about strategies to enhance the competence-based curriculum's effective implementation in Tanzania's secondary schools. The research methodology: A case study research design was used in the study. 112 participants from various educational categories, including District Education Officers (DEO), Quality Assurers (QA), heads of secondary schools and teachers, participated in focus groups and interviews to acquire the data. The study also employed a thematic approach to data presentation and analysis. Findings: The study's findings identified several strategies that can be used in Tanzania to successfully implement a competency-based curriculum: ensure that heads of schools regularly receive pedagogical leadership training, improve in-service teacher training, improve school-based indoor training, employ enough teachers, improve school infrastructure, provide enough teaching and learning materials, ensure effective partnership between schools and parents improve library services and improve use of information technology, improve school based assessment procedures and establishment of school-based quality assurance department. Unique Contribution to Theory, Practice and Policy: The findings of the study supported the constructivist theorists' claim that social interaction among students is an important factor in fostering meaningful learning. As an outcome, it will be possible to adequately apply the competency based curriculum in the classroom if there is a positive teaching and learning environment that is characterised by having sufficient teachers, teaching and learning resources and knowledgeable school leaders. The study recommended that both public and private schools keep up their efforts to hire enough teachers, increase and redevelop school facilities, install information and communication technology (ICT) infrastructures at every school and establish and strengthen initiatives aimed at training heads of schools and teachers in pedagogical leadership.